Manajemen Proyek Pengerjaan Pipa Air pada PT. X Menggunakan Metode CPM dan PERT - Wiranda, Fauzi Irfan; Murnawan, Hery (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
A project is a temporary activity that has a beginning and end specified in time and scope. To support the success of a project, project management needs to be carried out. In general, a project is held by a contractor. contractors who have the obligation to carry out work according to the plan, schedule the activities to be carried out, provide supporting tools for project implementation. One company operating in this field is CV. Andhika Kencana. Now CV. Andhika Kencana is carrying out work on several projects, one of which is the water pipe installation project at PT. X. This research aims to guarantee the water pipe installation project at PT. X is right in terms of cost, quality and time. This research uses 2 methods to analyze project work schedules, namely the Critical Path Method (CPM) and Project Evaluation And Review Technique (PERT). The results of this research show that the critical path on this project is A-B-C-D-G-H-K-L-M-N-O with different completion times. Using the CPM method, the project can be completed in a total of 65 working days, which is 1.15% faster than the normal time. Meanwhile, using the PERT method, the project can be completed in a total of 66.2 working days with a chance of 70.88%, which is 1.13% faster than the normal time.